Pemakaian Inhibator Sebagai Pengolah Air Umpan Boiler - Lelawati lelawati (MAJALAH TEKNIK SIMES, 2018)
Use boiler feed water (Boiler Feed Water) can be derived from water wells, water taps and water surface, tocondition the water according to standard either pH, Turbidity, silica and hardriess levels, as boiler feed the needfor early treatment (pretreatment) by adding substances certain chemicals (inhibitors) in order to procesperkerakan (scale) and corrosion in boilers can be protected and further the process of heat transfer (heat transfer)Can run better swith stream producton will be more qualified.